ASUHAN KEPERAWATAN DENGAN GANGGUAN RASA NYAMAN PADA PASIEN HIPERTENSI DENGAN TINDAKAN FINGERHOLD DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Sonia Angelina; Virginia Syafrinanda; Nina Fentiana; Resmi Pangaribuan (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2024)
Introduction: Hypertension is a condition in which a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality. WHO shows that around 1.13 billion people in the world suffer from hypertension, the number of people with hypertension continues to increase every year, it is estimated that in 2025 there will be 1.5 billion people with hypertension, and it is estimated that every year 10.44 million people die from hypertension and its complications. Research Objective: Implementing nursing care in the form of providing fingerhold actions to hypertensive patients who experience discomfort. Method: This research is descriptive with a case study approach of nursing care starting from assessment, diagnosis, intervention, implementation, and evaluation, which was carried out on two respondents aged >18 years who suffered from hypertension with discomfort. Fingerhold actions were carried out for 3 days on both patients at the Putri Hijau Class II Hospital, Medan, using nursing interventions according to SIKI (2018). Research Results: It was found that the provision of fingerhold action can reduce discomfort in hypertensive patients, after the action was carried out for 3 days on client 1 before the action was carried out with a pain scale of 6 (moderate), and after the action became 3 (mild). While in client 2, pain was obtained in the nape of the head before the action was carried out with a pain scale of 6 (moderate), and after the action became 3 (mild). Conclusion: The provision of fingerhold action carried out for 3 days can reduce discomfort in patients suffering from hypertension. Suggestion: Can increase knowledge in hypertensive patients about handling discomfort disorders.